Strategy Internationalization SMEs of Overlay Visualization Bibliometric Analysis: Experiential Marketing, Relationship and Digital Technology in increasing Consumer Satisfaction in Indonesia - Budi Utami; Imam Mukhlis; Danardana Murwani (Asian Journal of Community Services, 2023)
Indonesia is a country that is still developing today. However, when viewed from the internationalization process between countries, there has also begun to progress.  The purpose of this study is to look for various internationalization strategies carried out by MSMEs to increase consumer satisfaction in Indonesia. The factors found are experiential marketing, relationships, and digital technology.   The analysis used is the  Overlay Visualization Bibliometric. The result of this study is the relationship between experiential marketing, relationships, and digital technology which is still minimal for MSME actors in Indonesia.    Further needs to be held related to the development of internationalization strategies with other factors such as recommendations, emotional intelligence, risk performance, digital marketing, online shop, and competitive advantage with other country objects.